A numerical study of the relation between the acoustic generator geometry and the heat transfer conditions - Sebastian Rulik; Włodzimierz Wróblewski; Krzysztof Rusin (Archive of Mechanical Engineering, 2018)
Modern gas turbine systems operate in temperatures ranging from 1200°C to even 1500°C, which creates bigger problems related to the blade material thermal strength. In order to ensure appropriate protection of the turbine blades, a sophisticated cooling system is used. Current emphasis is placed on the application of non-stationary flow effects to improve cooling conditions, e.g., the unsteady-jet heat transfer or the heat transfer enhancement using high-amplitude oscillatory motion. The presented research follows a similar direction. A new concept is proposed of intensification of the heat transfer in the cooling channels with the use of an acoustic wave generator. The acoustic wave is generated by an appropriately shaped fixed cavity or group of cavities. The phenomenon is related to the coupling mechanism between the vortex shedding generated at the leading edge and the acoustic waves generated within the cavity area. Strong instabilities can be observed within a certain range of the free flow velocities. The presented study includes determination of the relationship between the amplitude of acoustic oscillations and the cooling conditions within the cavity. Different geometries of the acoustic generator are investigated. Calculations are also performed for variable flow conditions. The research presented in this paper is based on a numerical model prepared using the Ansys CFX-17.0 commercial CFD code.